The contribution of Ibn al-Awwam in botany and agriculture - Kamaruddin, Mohd Hider; Faris, Waleed Fekry (IIUM Press, 2011)
The main objective ofthis chapter is to discuss and deliberate on the contribution of Ibn AI-Awwam in relation to the advancement of botanical science and agriculture. The significance of this chapter is for the people especially the new generations to appreciate the findings and thinking of the people of historical age, particularly the Muslim's scientists and their works so that the people in the present state could mere develop a new thought or findings. The methodology adopted in this chapter is web base research and by looking into the ancient Islamic civilization and find out the contribution of an ancient Muslim's scientist in the field of Botany and Agriculture